Research of new mixed-chelate copper complexes with quinoxaline N 1,N 4,-dioxide derivatives and alanine as ligands, potential antimycobacterial agents - Belén Tarallo, M.; Costa-Filho, A. J.; Vieira, Ernanni D.; Monge, Antonio; Leite, Clarice Q. [UNESP]; Pavan, Fernando Rogério [UNESP]; Borthagaray, Graciela; Gambino, Dinorah; Torre, María H. (My University, 2009)
Three new mixed-chelate copper complexes with 3-aminoquinoxaline-2-carbonitrile N 1,N 4-dioxide derivatives and alanine as ligands were synthesized in solid state. The spectroscopic characterization (FTIR, EPR, UV-Vis) showed that copper coordinated through the amine and the N-oxide groups of the quinoxaline derivatives and the amine and carboxylate moieties from alanine forming a dimeric species. The tree complexes showed in vitro activity against M. tuberculosis H 37Rv (ATCC 27294) similar to that of ethambutol while they are inactive against E. coli and S. aureus.
Keywords: Antimycobacterial agents; Copper complexes; Quinoxaline derivatives